Parallel block codes for solving large systems of ordinary differential equations. (13th February 2006) - Majid, Zanariah Abdul; Suleiman, Mohamed B.
The two-point fully implicit block methods are developed for solving large systems of ordinary differential equations (ODEs) using variable step size on a parallel shared memory computer. The method calculates the numerical solution at two equally spaced points simultaneously within a block. The sequential and parallel performances of these methods are compared with the performances of the two-point block method using variable step size and order developed earlier by Omar (1999). For large problems, the parallel implementation produced a good speedup with respect to the sequential timing and hence better efficiency for the methods developed. The stability of the methods is also investigated.